First studies on the virulence spectrum of Finnish Drechslera avenae isolates - Jalli, Marja (MTT, 2004)
Leaf spot and seedling blight on oat (Drechslera avenae (Eidam) Scharif) is an important disease of oat (Avena sativa L.) particularly in areas with a cool climate. In Finland, leaf spot is the most significant disease of oat. Breeding oat for improved resistance to leaf spot is therefore a priority in the Finnish oat disease resistance breeding programme. For leaf spot disease breeding strategies to be successful, it is important to have information both on the pathogen population and also on possible resistance sources. 20 D. avenae isolates were collected from a total of seven oat genotypes grown at 12 separate locations across Finland. Single spore cultures were made and the aggressiveness and the virulence of the isolates were tested under greenhouse conditions on 20 different oat genotypes. The genotypes were selected based on the results of two hill plot tests conducted under field conditions utilising natural leaf spot infection. 18 of the 20 D. avenae isolates were viable enough for spore production and were tested in the greenhouse. All the isolates produced clear leaf spot symptoms on the oat genotypes examined. The isolates showed clear differences both in their aggressiveness and virulence. Genotypes Cc 3678 and Suregrain, which showed the highest resistance in field tests, were also resistant against all of the 18 isolates in the greenhouse test. However, genotype Dal gave a resistant response in the seedling test but was the most susceptible genotype under field conditions. The correlation between the results of the seedling and the adult plant test is discussed.
Keywords: Ka; oat; leaf spot; Drechslera avenae; virulence; resistance; Avena sativa